2021
DOI: 10.3991/ijim.v15i11.20133
|View full text |Cite
|
Sign up to set email alerts
|

A Software Security Optimization Architecture (SoSOA) and its Adaptation for Mobile Applications

Abstract: Security attacks become daily news due to an exposure of a security threat in a widely used software. Taking software security into consideration during the analysis, design, and implementation phases is a must. A software application should be protected against any security threat such as unauthorized distribution or code retrieval. Due to the lack of applying a software security standard architecture, developers may create software that may be vulnerable to many types of security threats. This paper begins b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Step 1: The collection of user reviews, after search and discussion we concluded to use the dataset from [32][33][34].…”
Section: Methodsmentioning
confidence: 99%
“…Step 1: The collection of user reviews, after search and discussion we concluded to use the dataset from [32][33][34].…”
Section: Methodsmentioning
confidence: 99%
“…The IoT comprising WSNs (Wireless Sensor Networks) WBANs (Wireless Body Area Networks) are playing a very essential role in numerous health-related issues and healthcare atmospheres [3][4][5][6], [29][30][31]. Smart homes, automated and hyper-connected homes, intelligent household systems, and devices including light bulbs, power outlets, thermostats, and other numerous applications are connected through the Internet which allows operating remotely.…”
Section: Over Of Iot Scope and Iot Architecturementioning
confidence: 99%
“…Whereas, agricultural IoT devices include green-house sensor systems, monitoring fields, and irrigation controllers. The streetlights water distribution systems are applications for city IoT domains [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the Android OS has emerged as the top mobile OS with a significant global market value and presence. Records have shown that more than a billion Android devices have been purchased, with Google Play alone accounting for an estimated 65 billion mobile software application downloads [3,4]. Consequentially, Android's increasing popularity and usage, as well as the development of third-party app stores, has rendered it vulnerable to a variety of malware [5].…”
Section: Introductionmentioning
confidence: 99%